A decoupler-free simple paper microchip capillary electrophoresis device for simultaneous detection of dopamine, epinephrine and serotonin. Issue 43 (6th July 2020) - Roychoudhury, Appan; Francis, Kevin Antony; Patel, Jay; Jha, Sandeep Kumar; Basu, Suddhasatwa
Abstract : This paper demonstrates a simplified configuration for capillary electrophoresis-amperometric detection using paper microfluidic chip for separation and simultaneous detection of three clinically relevant neurochemicals without using any decouplers. Abstract : This paper demonstrates a new and simplified configuration for capillary electrophoresis-amperometric detection (CE-AD) using a paper microfluidic chip incorporating inexpensive wax printing and screen printing based methods and then used for electrophoretic separation and simultaneous in-channel amperometric detection of three clinically relevant neurochemicals in a single run without using any decouplers. Detection of neurochemicals e.g., dopamine, epinephrine and serotonin is crucial for early prediction of neurological disorders including Parkinson's, Alzheimer's, dementia, as well as progressive neuro-psychiatric conditions such as depression, anxiety, as well as certain cardiovascular diseases. The plasma concentrations of such neurochemicals are as important as those present in cerebrospinal fluid (CSF) and can be useful for rapid and convenient biosensing. However, simultaneous detection of such neurochemicals in a complex mixture such as human serum requires their separation prior to detection. With the developed microchip, separation and detection of the neurochemicals were exhibited within 650 seconds without pre-treatment and the procedure was validated with spiked fetal bovine serum samples. Beside this, the developed paper microfluidic chip has potential to be integrated in point-of-care diagnosis with onsite detection ability. Moreover, the use of a straight channel capillary, a screen-printed carbon electrode without decoupler, in-channel amperometric detection and low sample volume requirements (2 μL) are shown as additional advantages.